Math, asked by shrivastavanehanshu, 5 months ago

solve the following question

Attachments:

Answers

Answered by Amitk408265
1

Answer:

Hope it will be helpful !

Step-by-step explanation:

Y/2-Y/3= 4+3

LCM of 3 and 2 =6

3Y - 2Y/6 = 7

Y/6=7

Y= 7*6

Y= 42

Answered by anjalipandeybbu
0

Step-by-step explanation:

Y/2 - 3 = Y/3 + 4

we take LCM of 2 in left side and. take LCM of 3 in right side

(Y - 6) / 2 = (Y + 12) / 3

so, 3×(Y - 6). = 2× (Y + 12)

therefore , 3Y - 18 = 2Y + 24

so, 3Y - 2Y = 24 + 18

so , Y = 42

Similar questions